Genotypes and haplotype combination of DCAF7 gene sequence variants are associated with number of thoracolumbar vertebrae and carcass traits in Dezhou donkey - Tianqi Wang; Xinrui Wang; Ziwen Liu; Xiaoyuan Shi; Wei Ren; Bingjian Huang; Huili Liang; Changfa Wang; Wenqiong Chai (Journal of Applied Animal Research, 2023)
Previous studies reported that DDB1 and CUL4 associated factor 7 (DCAF7) is associated with craniofacial, muscle, fat and bone growth and development. Therefore, the objective of this study was to explore genetic variation in the DCAF7 gene and its potential association with number of thoracolumbar vertebrae and carcass traits in Dezhou donkeys. Seven single-nucleotide polymorphisms (SNPs) were detected by targeted sequencing and Sanger sequencing in the intron region of the DCAF7 gene in 406 Dezhou donkeys. The polymorphism at g.48991059 T > G was significantly associated with hide weight (P < 0.05). g.48978712 T > C, g.48985896 A > G, g.48987539 C > T, g.48988058 A > G and g.48992171 C > T sites were associated with number of thoracic vertebrae (P < 0.05). Furthermore, linkage disequilibrium analysis showed that four of the seven SNPs of DCAF7 gene were strongly linked to each other and can be used as Tag SNP. Data analysis revealed that haplotype combination Hap2Hap4 (TCAGTTCC) had the highest length of thoracic vertebrae, it was significantly higher than that in haplotype combinations Hap1Hap2 (TTAAGTCC) and Hap1Hap3 (TCAGGTCT) (P < 0.05). Finally, the results of this study suggest that the polymorphisms of DCAF7 gene can be used as a molecular marker for donkey breeding.